Influence of TiO2 nano-particles on charge carrier transport and cell performance of PMMA-LiClO4 based nano-composite electrolytes. (10th January 2018) - Pal, P.; Ghosh, A.
Abstract: The plasticized PMMA-LiClO4 based solid polymer nano-composite electrolytes were prepared for different concentrations of TiO2 nano-particles using standard solution cast technique. The structure, glass transition temperature, thermal stability and particle size of these nano-composites have been studied by X-ray diffraction, differential scanning calorimetry, thermogravimetric analysis and transmission electron microscopic analysis respectively. The complex conductivity spectra have been measured in the frequency range of 0.01 Hz–2 MHz and analyzed using random barrier model. The contribution of the electrode polarization in low frequency region and at high temperatures has been taken into account during analysis. The temperature dependence of ionic conductivity and relaxation time has been found to obey the Vogel-Tammann-Fulcher relation. A maximum ionic conductivity of ∼3.0 × 10 −4 Scm −1 has been observed for the electrolyte with 1 wt% TiO2 nano-particles. The dielectric spectra have been analyzed using Havriliak-Negami function to understand the relaxation of charge carriers. The ion-ion and ion-polymer interactions have been studied using Fourier transform infrared (FTIR) spectra. Finally, the cycling performance of a coin cell of configuration graphite/PMMA-LiClO4 -30 wt% PC-1wt% TiO2 /LiCoO2 evaluated at 25 °C indicates suitability of the nano-composites as solid electrolytes for Li ion polymer cell.